PEMBELAJARAN SOMATIS AUDITORI VISUAL DAN INTELEKTUAL (SAVI) UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK ELEKTRO IKIP PGRI PADA MATA KULIAH RANGKAIAN ELEKTRONIKA - Hari Wibowo, Agus (Jurnal Pendidikan, 2012)
The grand mision of vocational school policy is to produce graduates who have national, regional and international competitive advantage. To guarantee the students of vocational school sufficient learning process, the vocational school teacher traning institution is obliged to provide the qualified lecturers, infrastrustures and teaching aids and materials. Among those requirements, students of vocational school teacher training institution should also be trained in such a way that they are skillful in handling students to face the working environment. This research is attempted to meet such demand by developing teaching process under Somatic Auditiry Visual and Intelectual Approach (SAVI) to train the students sensitive against the environment.Key words: Somatic Auditiry Visual and lntelectual Approach (SAVI), Competence, Achievement